Integrating Emergency Medical Services, Nursing, Radiology, and Public Health for Effective Disaster Response: A Systematic Review - A Al Otaifi, Abdullah Hamdan; Nasser Alharbi, Faris Muqbil; Alharbi, Bassam Saud Ghazai; H Alharbi, Mamdouh Hayis; Alharbi, Faisal Hamoud Shudayyid; Hamad Alharbi, Abdulmajeed Humaidi; Alanazi, Raed Saad Khamis; Almutairi, Eisi Mulfi Abdullah; Alharbi, Ahmed Jazaa Ateeq (Journal of Neonatal Surgery, 2025)
Most agencies involved in healthcare services and the respective stakeholders are looking for positive changes in the processes and policies to update the current services and provide funds and equipment to deal with current and future chronic ailments. This isn't easy in a developing country like Saudi Arabia, as the government has recently started looking after the service. This shows that there is a significant scope for improvement in healthcare-related services, especially during times of disaster and emergencies. This Present study will focus on integrating healthcare services in the country and present a detailed and systematic review. The duration of the study is from 2010 to 2025